Strengthening Families: Parental Resilience - Larry F. Forthun; Samantha Carannante; David C. Diehl (EDIS)
Through building resilience, parents and other family members will be better prepared to manage the inevitable challenges in life. The strategies recommended in this 3-page fact sheet can help you further develop these positive attributes. Written by Larry F. Forthun, Samantha Carannante, and David C. Diehl, and published by the UF Department of Family, Youth and Community Sciences, December 2011.